2019
DOI: 10.1007/s10342-018-01160-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pollutant fog deposition on the wood anatomy of subalpine Norway spruce

Abstract: In recent decades, significant changes have been observed in the atmospheric pollutant emissions and deposition in the mountain regions of Central Europe. Pollution caused significant deforestation, but the level of tree damage differs, even between neighboring locations. Thus, it is particularly important to examine the relationships between pollutant deposition rate and detrimental changes in the subalpine spruce ecosystems, and to correlate these with the intensity and structure of pollutant deposition. Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
1
8
0
1
Order By: Relevance
“…These results are in contradiction to the data presented so far that were related to seasonal events, after which the trees returned to their previous condition or could even increase their growth rate [33,34,57]. The phenomenon of reduced cambium activity is generally considered to be a tree's response to extreme environmental factors such as drought, fire, frost, flooding, environmental pollution, or urban habitat [13,29,31,58,59]. Eventually, the cessation of cambium was observed as a result of significant stress, e.g., stem girdling [60].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These results are in contradiction to the data presented so far that were related to seasonal events, after which the trees returned to their previous condition or could even increase their growth rate [33,34,57]. The phenomenon of reduced cambium activity is generally considered to be a tree's response to extreme environmental factors such as drought, fire, frost, flooding, environmental pollution, or urban habitat [13,29,31,58,59]. Eventually, the cessation of cambium was observed as a result of significant stress, e.g., stem girdling [60].…”
Section: Discussionmentioning
confidence: 70%
“…Much less is known about the differentiation of the second conductive tissue, i.e., secondary phloem, in association with cambial activity, wood differentiation or tree phenology [20][21][22][23][24][25]. Moreover, cambial activity and the differentiation of secondary conductive tissues (especially wood) depend on many factors, both intrinsic (e.g., hormones and gene expression; [16,26]) and extrinsic (climatic and non-climatic; [27][28][29][30][31]). One of the non-climatic factors is the attack of defoliating insects, which can lead to a decrease in the width of growth rings as a consequence of fewer cambial divisions and fewer elements of secondary xylem thus being formed [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The width of the annual rings was analyzed over three decades: to intense pollution of the environment with hazardous substances (1950)(1951)(1952)(1953)(1954)(1955)(1956)(1957)(1958)(1959)(1960), during intense pollution (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990) and after pollution (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010). The studies revealed that the narrowest annual rings of spruce formed in 1980s in the regions where the mist was the main source of the sedimentation of the polluting substances (Myskow et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among the internal factors, the greatest effects are related to the species of the tree (Magnuszewski et al, 2015;Sitková et al, 2018, Burri et al, 2019, inherited individual variability, age and fruiting (Ding et al, 2017;Latreille et al, 2017;Buras et al, 2018). The most influential external factors are latitudinal, longitudinal and height gradients of the conditions of growth locations of the trees (Magnuszewski et al, 2015;Matskovsky, 2016;Chen, 2017;Gao et al, 2018), air temperature and precipitations (Natalini et al, 2015;Rybníček et al, 2016;Rozas & Olano, 2017), wind (Dinulica et al, 2016), mist (Myskow et al, 2019), soil conditions (Mendivelso et al, 2016), phytocenosis relations (Latreille et al, 2017;Moreau et al, 2019), catastrophes of various origin: fires (Gao et al, 2017), windthrows and windsnaps (Holeska et al, 2016), diseases, attacks of harmful insects (Brygadyrenko, 2016;Faly et al, 2017;Van de Gevel et al, 2017;, summer and winter droughts, emissions of CO 2 (Cavlovic et al, 2015;Svobodova et al, 2019), heavy frosts during snowless periods (Su-vanto et al, 2017), and also agricultural activity by humans (Montoro Girona et al, 2016;Tyukavina et al, 2017;Wang et al, 2018). Forest felling, meso-and macro scale effects on the environment lead to negative tendencies of radial increment and deforestation (Rodriguez-Caton, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Очікується, що частота і масштаби природних порушень, а також посухи збільшаться із змінами клімату [18]. Довготривалі зміни клімату істотно впливають на ріст дерев та поширення видів в Європі [15].…”
Section: вступunclassified